Pemanfaatan Ikan sebagai Bahan Baku dalam Meningkatkan Perekonomian UKM di Dusun Batu Rimpang Utara - Yuniar Affandy; Salmi Yuniar Bahri; Masbullah Masbullah; Pitriadi Pitriadi; Tahur Ramdani (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2024)
North Batu Rimpang Hamlet is known as a center for fresh fish trading; however, its utilization as a raw material for processed fish products remains low. This study aims to analyze the use of fish in improving the economy of Small and Medium Enterprises (SMEs) in North Batu Rimpang Hamlet through fish processing training. The method used is descriptive qualitative, including interviews, observations, and documentation involving SME actors. The results show that the training provided on processing fish into two types of products—fish nuggets and shredded fish—successfully increased the knowledge and skills of the SME participants. They reported higher incomes and better market access after attending the training. Moreover, more innovative and competitive processed fish products have begun to enter the market, demonstrating the program's success in supporting the local economy.